PENGARUH WORD OF MOUTH, BRAND IMAGE, DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PRODUK INSTINCT FOOTWEAR (STUDI PADA KONSUMEN INSTINCT FOOTWEAR KOTA SAMARINDA) - Yan Khanafi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to see the influence of Word of Mouth, Brand Image, and Brand Trust on the Purchase Decision of Instinct Footwear Products in Samarinda City. Word of Mouth (X1), Brand Image (X2), and Brand Trust (X3) are used as independent variables while Purchase Decision (Y) is the dependent variable. Primary data obtained by interviewing 130 respondents using a questionnaire. Secondary data obtained by making field observations. Data analysis used multiple linear regression techniques with the help of statistical software SPSS version 22. The results showed that the independent variables consisting of Word of Mouth, Brand Image, and Brand Trust (simultaneously) significantly influence Purchase Decisions and (partially) each of the two independent variables Brand Image and Brand Trust affect the Purchasing Decision. Meanwhile, Word of Mouth (partially) has no significant positive effect on Purchasing Decisions. Instinct Footwear can continue to develop a brand image that has been well attached to local scale brand products, a good brand image will generate a positive word of mouth, then increase and increase brand trust from consumers by continuously improving product quality and providing positive value. will create a sense of security and trust in the company or product being marketed. These three roles are very important simultaneously to achieve competitive advantage in business.